Queer Theory and Feminist Methods: A Review - Cuklanz, Lisa; Erol, Ali (Investigaciones Feministas (Feminist Research), 2020)
Feminist research methodologies seek to conduct research that aligns with the political and social project of feminism. These research methodologies specifically focus on women’s voice, experiences, and contributions, center a feminist perspective and adopt premises and assumptions of a feminist worldview. Some of these premises—raising critical consciousness, encouraging social change, and emphasizing a diversity of human experience related to gender at the intersection of race, sexuality, and other categories of identity—align with the premises and assumptions of queer theory. Since both feminist and queer research methods aim to centralize the experiences of people marginalized under racist, sexist, heterosexist, patriarchal, and imperialist conditions, both methods seek decentralization of and liberation from such experiences in research methodologies. While this paper will briefly discuss these important points of alignment between feminist methods and queer theory, the main purpose will be to distinguish these two broad approaches and to outline what queer theory additionally brings to the table.